The Change of Poetic Generations in Lithuanian Soviet Poetry: a Semantic Aspect - Balsevičiūtė-Šlekienė, Virginija (Acta humanitarica academiae Saulensis, 2025)
The article analyses the lyrics from the 7th to the 9th decades. The aim is to reveal how and when the main layers of meanings were formed, how the inner structures changed, also to highlight poetical dominants. It was revealed that the main semantic lyrical structures began to take form in the sixties. Poetry based on peasant culture prevailed till the eighties. We can recognise the tradition of Land poets in it. The generation of Justinas Marcinkevičius, Jonas Juškaitis, Marcelijus Martinaitis achieved their highest level in the eighties, when its esthetical and ethical attitudes were framed. This generation created the double semantic model, in which the elevation of those, who affirmed the origins of existance, prevailed while emphasizing the ethical values (this elevation can be callled the ethics of authenticity) and the critical approach to its time was founded, as much as it was allowed by censorship. After the debut of the second generation (Algimantas Verba, Vladas Braziūnas, Stasys Jonauskas and others), we can observe the further development of this tradition. Its modern equivalent, the generation of Sigitas Geda, Vytautas Bložė, Leonardas Gutauskas, Albinas Žukauskas, who experimented with the treasures of myth, history, religion and created the complicated world vision system stand out in the context of Soviet poetry. In the seventies the generation of Antanas A. Jonynas, Gintaras Patackas, Almis Grybauskas, Vytautas Rubavičius created the contraversive model of artistic world, digressing from the dominant lyrical model, but providing new chances for lyrical evolution. In their poetry we find the poetical world, which was already losing the national colouring and decreasing to a great extent the importance of the agrarian world. The seventies can be called the time of the most intensive development of arstistic structures, because precisely then the main semantic divisions occurred. The paradigm of land deprivation was dominant in Soviet poetry. Every poetic generation emphasised it in its own different way. The search for authentical existance, the longing for ethical values were important to the poetry, which was restricted by ideology and censorship.